A review: fourier transform infrared application on bioactive compound - Che Noh, Che Hafizah (2015)
Natural products are a promising area for researchers from various fields since there are many benefits exhibit from the application of the natural product especially in food application and medicinal purposes. Bioactive compounds, the natural products that mostly found in fruits and vegetables, has shown an increasing demand as one of the important sources for the medicinal purposes such as for the formulation of drug and alternatives herbal medicines. The bioactive compound present in food (e.g. meat) and beverages (e.g. wine) have helped researchers and industries to improve quality identification. FTIR recently has become well-accepted method used for the identification of bioactive compounds since it offers simple preparation sample and high analysis speed. Therefore, we highlight the needs for the identification of bioactive compounds and the current research on the identification of bioactive compounds performed using the FTIR.